(3JaSjQ GGdCdaGX GdWHjI hGddZhjI hGdhGbYI aj GdcJGH GdefUhQis - (3CHh LYaQ CMeO Hf eMeO Hf GdMSfs; (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh LYaQ gPG JaSjQ GdCdaGX GdWHjI hGddZhjI GdhGbYI ai GdcJGH GdefUhQi , hgj eHhHI Ydi MQha GdeYLe , HMSH GSJYeGd Cgd HdO GdeZQH dgG s
(3BNQgG (B:s
(3jQhM , jSei KeQI GdJaGM , hjSei HGdeZQH (B: (3HWjN GdMQG , hefg CUd jTHg CUdg UhQ GdfGS THgG cKjQkG MJi cCfg eUfhY eMce hefg PcQ hCfKi hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B29 - (3U(B79s
(3eQJHI Ydi MQa GdeYLes
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B61 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs